Key Concepts in Literary Theory, Second Edition. - Wolfreys, Julian (Edinburgh University Press, 2006)
Presents the student of literary and critical studies with a range of definitions of the significant terms and concepts used in psychoanalytic, poststructuralist, Marxist, feminist, and postcolonial literary studies. This volume also provides useful discussions of the main areas of literary, critical and cultural theory.